Virulence characteristics and antimicrobial resistance of Aeromonas veronii biovar sobria 312M, a clinical isolate - Prediger, Karoline de C. (Braz J Microbiol, 2019)
Aeromonas are bacteria widely distributed in the environment, and some species are able to cause infections in humans, of which diarrhea is the most common. The objective of this study was to evaluate the presence of virulence and antimicrobial resistance associated characteristics in A. veronii biovar sobria strain 312M isolated from diarrheal stools. For this, the genome sequencing and phenotypical tests were performed. The draft genome annotation revealed several complete pathways associated with carbon metabolism and a mucin-desulfating sulfatase which may contribute to intestine colonization, and a large number of virulence-associated genes encoding structures associated with adhesion, toxins, and secretion systems. The strain exhibited swimming and swarming motility, biofilm formation, and hemolytic activity. It was resistant to ampicillin, ampicillin/sulbactam, and amoxicillin-clavulanic acid. Although a cphA gene encoding a narrow-spectrum carbapenase was identified in the strain genome, no carbapenemase activity was detected in the antimicrobial susceptibility test. When compared with other A. veronii with complete genomes, the main differences in virulence characteristics are related to lateral flagella and type III and VI secretion systems; the antimicrobial resistance spectrum also varied among strains. The results indicated that A. veronii biovar sobria 312M presents high virulence potential and resistance to limited classes of antimicrobials.